MENGELOLA PENDIDIKAN MULTIKULTURAL: Studi Etnografi di SMA Sultan Iskandar Muda Kota Medan - As’Ad, As’Ad; Firmansyah, Firmansyah; Fridiyanto, Fridiyanto (Universitas Islam Negeri Sumatera Utara Medan, 2021)
This article presents a good practice of a multicultural education concept in Medan City, which is known as a multicultural city. This study uses an ethnographic approach. Research findings include that at the Iskandar Muda School there are all students from various ethnicities, religions, and economies who can carry out an egalitarian education. Furthermore, the idea of multiculturalism appears in the physical form of the Iskandar Muda school which has houses of worship from various religions, there are mosques, churches, temples and temples that are built permanently and side by side and are located within the school environment. Then there is also a joint class, where students from different religions: Islam, Christianity, Buddhism, Hinduism and Confucianism become one when studying religion. In this joint class, each teacher explains the material that is delivered together and with shared material, for example, the material of affection. All religions teach love. Each teacher explains material related to love and affection.Multicultural Education, Moderat Young Generation, Good Practices, Medan City